Whole-Genome Phylogenetic Analysis Reveals a Wide Diversity of Non-O157 STEC Isolated From Ground Beef and Cattle Feces - Gutiérrez, Sebastián; Díaz, Leonela; Reyes-Jara, Angélica; Yang, Xun; Meng, Jianghong; González-Escalona, Narjol; Toro, Magaly (Frontiers in Microbiology, 2021)
Shiga toxin-producing Escherichia coli (STEC) cause foodborne outbreaks that can lead to complications such as hemolytic uremic syndrome. Their main reservoir is cattle, and ground beef has been frequently associated with disease and outbreaks. In this study we attempted to understand the genetic relationship among STEC isolated in Chile from different sources, their relationship to STEC from the rest for the world, and to identify molecular markers of Chilean STEC. We sequenced 62 STEC isolated in Chile using MiSeq Illumina. In silico typing was determined using tools of the Center Genomic Epidemiology, Denmark University (CGE/DTU). Genomes of our local STEC collection were compared with 117 STEC isolated worldwide through a core genome MLST (cgMLST) approach, and we also searched for distinct genes to be used as molecular markers of Chilean isolates. Genomes in our local collection grouped based on serogroup and sequence type, and clusters were formed within local STEC. In the worldwide STEC analysis, Chilean STEC did not cluster with genomes of the rest of the world suggesting that they are not phylogenetically related to previously described STEC. The pangenome of our STEC collection was 11,650 genes, but we did not identify distinct molecular markers of local STEC. Our results showed that there may be local emerging STEC with unique features, nevertheless, no molecular markers were detected. Therefore, there might be elements such as syntenic organization that might explain differential clustering detected between local and worldwide STEC.